State and prospects of the development of family forms of care in modern Ukraine - Tiurina, Tamara; Kinash, Orest (Social work and education, 2023)
In the article, based on the analysis of the activity of experimental projects and legal acts in Ukraine, the essence and peculiarities of the form of education of orphans and children left without parental care are characterized. The family environment remains the most optimal form of raising orphans for their communication in later life. The experience of popularizing the adoption of social orphans into a family environment for upbringing has been studied. The main directions of the spread of family forms of education in Ukraine are given. The problem of raising orphans who are in state care institutions and the need to introduce innovative approaches to provide professional help to orphans based on scientifically based concepts of education are updated. An overview of scientific research by modern scientists is presented, which highlight the historical aspects of the problem of guardianship and education of orphans in educational institutions in Ukraine. Officially recognized forms of family upbringing of orphans and children deprived of parental care are considered.